2014
DOI: 10.1002/lsm.22243
|View full text |Cite
|
Sign up to set email alerts
|

Two‐step irradiance schedule versus single‐dose tramadol sustained‐release tablets for pain control during topical 5‐aminolevulinic acid‐photodynamic therapy of condyloma acuminatum in Chinese patients: A randomized comparative study

Abstract: Pain in the two-step irradiance protocol is irradiance-dependent. The two-step irradiance approach produces significant benefits over analgesics during the initial stages of therapy but analgesics offer significant benefits thereafter. There are potential benefits of combining the two approaches in minimizing ALA-PDT-induced pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Previous studies on PDT of CA showed that the use of 31.8 mW/cm 2 irradiation can significantly reduce the pain during the initial treatment . Studies on PDT of basal cell carcinoma and Bowen's disease suggested that the irradiance close to 50 mW/cm 2 is most likely to cause pain .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on PDT of CA showed that the use of 31.8 mW/cm 2 irradiation can significantly reduce the pain during the initial treatment . Studies on PDT of basal cell carcinoma and Bowen's disease suggested that the irradiance close to 50 mW/cm 2 is most likely to cause pain .…”
Section: Discussionmentioning
confidence: 99%
“…The higher the irradiance is, the stronger the pain severity . Mchepange et al found that in the two‐step irradiance schedule for PDT of CA, the pain could be felt at 5 minutes of treatment, became sharper with time and gradually stabilized within 10–20 minutes. Consistent with others, our results showed that NRS score was the lowest at the first 5 minutes and rose evidently within 10–20 minutes until the plateau appeared.…”
Section: Discussionmentioning
confidence: 99%
“…ALA photodynamics is a new method for the treatment of skin diseases in the clinic. It uses photosensitive drugs and laser activation treatment principles to destroy the focal tissue [ 5 , 6 ]. This study mainly explores the clinical efficacy and safety of the carbon dioxide laser combined with ALA photodynamics in the treatment of CA.…”
Section: Introductionmentioning
confidence: 99%
“…By adjusting the light irradiance intensity and dose during PDT, a two-step irradiance schedule (2-SIS) was proposed and it has been reported to relieve pain during PDT significantly on non-melanoma skin cancer (NMSC) and condyloma acuminatum (CA) with similar clinical efficacy to c-PDT by many pieces of literature. [5][6][7] However, pain during 2-SIS PDT (usually moderate pain) [5][6][7] is still a challenge for most patients. According to the famous psychological "peak-end rule," 8 individuals' memories of medical interventions are accurately predicted by averaging the highest level of pain (the peak) recorded during an episode and the pain experienced at the end of the procedure.…”
Section: Introductionmentioning
confidence: 99%